The effect of passion on the engagement of university students specializing in DanceSport: the moderating role of gender - Huang, Ziyou; Zhu, Jiamin; Yuan, Yuxin; Li, Xiaofen (Frontiers in Psychology, 2025)
ObjectivesThis study aims to investigate the effect of passion on DanceSport engagement (DSE) of college students majoring in DanceSport, and to examine the moderating effect of gender.MethodsWe investigated 714 college students majoring in DanceSport with Passion Scale and Athlete Engagement Questionnaire from major sports institutes in China and Beijing Dance Academy.ResultsPassion was positively correlated with DSE (r = 0.651, p < 0.01). Among college students specializing in DanceSport, training time shows a significant positive correlation with education level, gender, passion, and DSE (p < 0.05). However, education level and gender had no correlation between passion and DSE (p > 0.05). Hierarchical regression analysis indicates that passion had a positive predictive effect on DSE (β = 0.677, p < 0.001). Gender had a positive moderating effect in the relationship between passion and DSE (β = −0.258, p < 0.001). Simple slope analysis revealed that the predictive effect was stronger for males (simple slope = 0.791) than for females (simple slope = 0.533) (p < 0.001).ConclusionThe discovery of the gender moderation effect broadened the dual model of passion, suggested that passion mechanisms differ based on the gendered nature of sports, offering a theoretical basis for nurturing DanceSport talent. For boys, enhancing DSE can involve boosting goal motivation for technical breakthroughs, increasing emotional expression training, and organizing simulated competitions. For girls, creating a cross-school dancer resource pool, implementing a “dual selection” mechanism, and boosting artistic expression and autonomy support can help overcome structural barriers and promote DSE.